Pengaruh Metode Pembelajaran Problem Solving Terhadap Kemampuan Membaca Kritis Siswa Kelas VIII SMPN 4 Marioriawa (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This study aims to describe the effect of problem solving learning method on critical reading ability of grade VIII students of SMPN 4 Marioriawa. This research is a quantitative research with one group pretest-posttest design. This research involved VIII grade students of SMPN 4 Marioriawa totalling 35 people. The data collection technique in this study used a multiple choice test totalling 20 questions. The results of data analysis showed that: (1) the critical reading ability of grade VIII students of SMPN 4 Marioriawa before the application of problem solving learning method was categorised as low with an average score of 10.37; (2) the critical reading ability of grade VIII students of SMPN 4 Marioriawa after the application of problem solving learning method was categorised as high with an average score of 16.26; and (3) the results of hypothesis testing showed that the sig. (2-tailed) value of 0.000 <0.05, so it is concluded that there is an effect of problem solving learning method on critical reading ability of grade VIII students of SMPN 4 Marioriawa.